Dynamic regulation of canonical TGFβ signaling by endothelial transcription factor ERG protects from liver fibrogenesis - Dufton,NP; peghaire,CR; Osuna-Almagro,L; Raimondi,C; Kalna,V; Chuahan,A; Webb,G; Yang,Y; Birdsey,GM; Lalor,P; Mason,JC; Adams,D; et al. (Nature Communications, 2017)
The role of the endothelium in protecting from chronic liver disease and TGFβ-mediated fibrosis remains unclear. Here we describe how the endothelial transcription factor ETS-related gene (ERG) promotes liver homoeostasis by controlling canonical TGFβ-SMAD signalling, driving the SMAD1 pathway while repressing SMAD3 activity. Molecular analysis shows that ERG binds to SMAD3, restricting its access to DNA. Ablation of ERG expression results in endothelial-to-mesenchymal transition (EndMT) and spontaneous liver fibrogenesis in EC-specific constitutive hemi-deficient (ErgcEC-Het) and inducible homozygous deficient mice (ErgiEC-KO), in a SMAD3-dependent manner. Acute administration of the TNF-α inhibitor etanercept inhibits carbon tetrachloride (CCL4)-induced fibrogenesis in an ERG-dependent manner in mice. Decreased ERG expression also correlates with EndMT in tissues from patients with end-stage liver fibrosis. These studies identify a pathogenic mechanism where loss of ERG causes endothelial-dependent liver fibrogenesis via regulation of SMAD2/3. Moreover, ERG represents a promising candidate biomarker for assessing EndMT in liver disease.